Air Filtration Technology in Reducing the Risk of Public Health Disorders - Ramadhan Tosepu; Inun Inun; Sitti Fadillah; Nur Zana; Nudjul Kila Ane Ode (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Air pollution is a major environmental and public health concern resulting from industrial activities, transportation, and fossil fuel combustion. Increasing population growth and economic development contribute to higher emissions of pollutants, including particulate matter, carbon monoxide, sulfur dioxide, nitrogen oxides, and volatile organic compounds. Exposure to these pollutants is associated with respiratory diseases, cardiovascular disorders, and impaired cognitive function, particularly among vulnerable populations such as children, older adults, and individuals with chronic illnesses. Objective: This study aimed to evaluate the effectiveness of air filtration technologies in reducing exposure to air pollutants and mitigating associated health risks. Methods: A literature review was conducted using journal articles, research reports, and secondary data from international and national health organizations. Relevant studies on air pollution and filtration technologies were systematically analyzed. Results: The review indicated that both outdoor and indoor air pollution significantly affect public health. Air filtration technologies, including HEPA filters, electrostatic filtration systems, and optimized ventilation designs, reduced airborne pollutant concentrations by up to 90–95% in industrial and healthcare settings. Their effectiveness depends on appropriate design, maintenance, and operational practices. Conclusion: Air filtration technology is an effective strategy for reducing pollution-related health risks. However, its successful implementation requires supportive policies, public awareness, and multisectoral collaboration to achieve sustainable environmental health outcomes. Keywords: air pollution, air filtration technology, public health, pollutants, literature review